Spatial and temporal variability of mobile macro-invertebrate assemblages associated to coralligenous habitat - BEDINI, R.; BONECHI, L.; PIAZZI, L. (Mediterranean Marine Science, 2014)
The study aimed to investigate patterns of spatial and temporal variability of mobile macroinvertebrate assemblages associated to coralligenous habitat. A multi-factorial sampling design was used to test the hypotheses that the structure of assemblages and their spatial and temporal variability changed in relation to substrate inclination. Moreover, macroalgae and sessile macro-invertebrates were also investigated in order to detect eventual relationship between sessile and mobile assemblages. A total of 236 mobile macro-invertebrate taxa were identified, among them 2 Platyhelminthes, 4 Sipuncula, 6 Nemertea, 27 Mollusca, 86 Annelida, 103 Arthropoda, 8 Echinodermata. Results of the study showed that mobile macro-invertebrate assemblages of coralligenous habitat were little influenced by the inclination of substrate and by the morphology of sessile organisms, as patterns of variation were different between the two assemblages. Mobile macro-invertebrate assemblages changed among sampling dates within one year period and they showed high variability at the spatial scale examined.